Menguak "Kebutaan Mitigasi" di Pantai Serambi Deli:Analisis Ekolinguistik dan Etnosains Terhadap Kepunahan Istilah Lokal Penanda Alam - Nazwa Annisa; Adira Cahya; Putri Wahyuni Sitohang; Agnes Falensia Lumban Gaol; Nurita Rahmani; M. Oky Ferdian Gafari (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Rapid coastal environmental changes have placed local communities vulnerable to various ecological risks. This study aims to explore the environmental risk perceptions of coastal communities in the Serambi Deli Coast area through the lens of ethnoscience and language analysis with an ecolinguistic approach. The method used was qualitative-ethnographic, including participant observation and in-depth interviews with community leaders selected purposively based on their knowledge and experience of the coastal environment. The study found three main findings. First, there is a phenomenon of Ecological Language Loss in the general coastal community, where local vocabulary for interpreting natural signs has disappeared due to cultural shifts and modernization. Second, this ecological knowledge is not completely extinct, but rather stored exclusively in the linguistic system of the Orang Laut community, which is highly dependent on the sea but isolated from the wider coastal community. Third, a survey of the younger generation revealed a very high level of ignorance of local terms for natural markers, indicating a Disruption of Intergenerational Knowledge Transmission, resulting in the younger generation experiencing "mitigation blindness" that potentially increases their vulnerability to disasters. This study concludes that local community languages ​​are living archives of ecological risk knowledge that is now on the verge of extinction. These findings underscore the urgency of documenting and revitalizing indigenous knowledge as an integral part of participatory and contextual disaster mitigation policies.